(The ultimate sticker book) Shark & whale (Dorling Kindersley Publishing Inc. New York, 1994)
Shark & Whale is an engaging educational book that explores the fascinating world of these magnificent ocean creatures. Through vivid images and accessible text, the book delves into the differences and similarities between sharks and whales, highlighting their anatomy, behaviors, habitats, and roles in the marine ecosystem. With close-up photography and detailed facts, readers will gain insight into the life cycles, feeding habits, and unique traits of various species of sharks and whales, making it a captivating resource for young readers and anyone interested in marine biology.